(untitled) (Materiali di Estetica. Terza serie, 2024)
This paper encapsulates a lecture delivered during the 2024 ‘Negative Emotions’ conference series at the Corrente Foundation. It aims to provide an overview of current research and scholarly interest in negative emotions, particularly the sublime, rather than a comprehensive analysis. The discussion is anchored in eighteenth-century theoretical frameworks, serving as a basis for exploring the evolution and reinterpretation of these ideas in modern academic discourse. The eighteenth century was pivotal for the philosophical examination of the sublime. Beginning with the ideas of Jean-Baptiste Du Bos (1719), Edmund Burke’s 1757 treatise on the sublime and beautiful distinguished the sublime as an experience that evokes a profound emotional response, both fearsome and exhilarating. In contemporary research, the sublime remains a significant area of interest, intersecting disciplines such as psychology, aesthetics, and neuroscience. Recent studies employing neuroimaging techniques have shown that experiences of the sublime activate neural pathways associated with both fear and pleasure, highlighting its complex nature. Additionally, immersive VR environments are used to evoke feelings of awe and the sublime, providing insights into how modern technology can replicate and study profound emotional experiences.